Intergenerational return to human capital - Paul J. Devereux (IZA World of Labor, 2014)
Governments invest a lot of money in education, so it is important to understand the benefits of this spending. One essential aspect is that education may make people better parents and thus improve the educational and employment outcomes of their children. Interventions that encourage the educational attainment of children from poorer families will reduce inequality in current and future generations. In addition to purely formal education, much less expensive interventions to improve parenting skills, such as parental involvement programs in schools, may also improve child development.
Keywords: J24; J18; 330; education; intergenerational mobility; child development